The Trend and Factors of Residential Auction Market in Gombak, Selangor: Residential Auction - Omar, Nooraisyah; Mohsen, Masfaliza; Shamsudin, Zarina; Omar, Ismail (Research in Management of Technology and Business, 2021)
In the recent growth of property market in Selangor, auction has become a popular sales mechanism when there is increasing exposures of this market sector towards society. The rationale behind why residential properties are being put up for auction is various yet heterogeneous. The unavailability of published data on the number of auctioned residential property makes it questionable for property players to know the status of residential sub-sector in auction market. The overall purposes of this study are to analyse the trend of residential auction market in Gombak from 2015 to 2019 and to identify the factors that influenced the trend. In achieving the objectives, reviewing transaction data for auctioned residential properties will be carried out as well as interview with professionals relevant to the sector (Licensed Auctioneer, Valuation Officer and Land Office officer in-charge for public auction) to identify the factors influence the auction market trend in Gombak District. The outcome data will be presented by using graphical medium to provide a clear data visualisation. This study focused on auctioned residential data in Gombak district from year 2015 until 2019. This study is expected to be able to provide structured information on transaction data of auctioned residential properties in Gombak as well as factors that influenced the market trend.